2021
DOI: 10.1371/journal.pone.0254212
|View full text |Cite
|
Sign up to set email alerts
|

Management of maternal depression: Qualitative exploration of perceptions of healthcare professionals from a public tertiary care hospital, Karachi, Pakistan

Abstract: The lack of implementation and routine screening of management techniques at tertiary care hospitals leads to an increased burden of maternal depression. The consequences are borne emotionally, physically, and mentally by the mother, the child, the overall family, and society. Hence, it is vital to contextualize this mental disorder to design and implement effective healthcare interventions. The study is aimed to assess the knowledge and practices of healthcare professionals, in a tertiary care setting, who de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, patients with hypothyroidism during pregnancy may worry too much about their own health problems and the health of their fetus, affecting them psychologically and potentially leading to negative thoughts and emotions. [ 11 , 12 ] (2) Education level and economic income: the lower the education level, the worse the economic conditions, and the more prone to depression an individual becomes. Pregnant women do not have a good understanding of their own health or that of their fetus and can be overly pessimistic.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with hypothyroidism during pregnancy may worry too much about their own health problems and the health of their fetus, affecting them psychologically and potentially leading to negative thoughts and emotions. [ 11 , 12 ] (2) Education level and economic income: the lower the education level, the worse the economic conditions, and the more prone to depression an individual becomes. Pregnant women do not have a good understanding of their own health or that of their fetus and can be overly pessimistic.…”
Section: Discussionmentioning
confidence: 99%
“…Depression during pregnancy can have repercussions in later life for the mother and present as eating disorders, post-traumatic stress disorder, and personality disorders [21]. Furthermore, despite the high prevalence of depression in low-and middle-income countries, mental health management is stigmatized [22][23][24]. Such stigma may compound lower self-esteem issues in these women, and decrease their help seeking behaviour [25].…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that managing women with perinatal depression is well-known among midwives in high-income countries (HIC) [ 8 , 23 ]. In LMICs however, stigmatization and a lack of awareness of the care and management of perinatal depression among HCPs have been reported [ 24 , 25 ]. A substantial number of studies have revealed that perinatal women have been subjected to disrespectful and abusive care by HCPs, especially during childbirth [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%